The real-time determination of d- and l-lactate based on optical weak measurement. Issue 16 (8th April 2019) - Qiao, Zhen; Shi, Lixuan; Guan, Tian; Xu, Yang; Guo, Cuixia; Li, Dongmei; He, Yonghong; Ji, Yanhong
Abstract : A simple transmission optical rotation (OR) configuration based on weak measurement was developed for the real-time determination ofd - andl -lactate. Abstract : A simple transmission optical rotation (OR) configuration based on weak measurement was developed for the real-time and relatively high precision determination of chiral molecules. According to the theory of optical weak measurement, the shift of the central wavelength of output spectra bears a close relationship with the angle of pre-selected polarization in the frequency domain. Hence, by altering the pre-selected polarization state with the OR, the lactate enantiomers can be detected. The optical activity is not only relative to the concentration of the tested chiral sample but also can be quantitatively analyzed via the shift of the central wavelength of output spectra. Meanwhile, it can be collected in real time. Since the proposed weak measurement system is not sensitive to the refractive index change, it works well in complicated circumstances. Against this background, the experiments of determination ofd - andl -lactate were conducted to obtain the optical activity ofd - andl -lactate. The experiments showed that the two isomers of chiral lactate exhibited opposite responses. A resolution of 5.7 × 10 −4 ford - andl -lactate determination was reached based on the system, which shows a relatively high sensitivity about 3 orders of magnitude higher than that of traditional polarimeters. Moreover, the proposed method is successfully applied for the detection ofl -lactate in lactate cream samples. Furthermore, the weak measurement still has great advantages, such as real-time detection, a simple setup, high robustness, high stability and low cost. As a promising method, this real-time and high resolution determination approach matters much in clinical diagnosis, food safety and biological systems.